KEDUDUKAN ,TUGAS DAN PERTANGGUNG JAWABAN WAKIL PRESIDEN MENURUT UUD 1945 - Indrastuti, Lusia (Wacana Hukum, 2010)
Abstract Vice president is a government officer one level below president. Vice president is stated by a constitution of a state to accompany the president when he is on his official duty in other country or when the president returns his position either for a widrawal or permanent reason such as a death. The article 4, clause (2) of Undang-Undang Dasar 1945 states that president in his duties is assisted by a vice president in the Republic of Indonesia state structure system. The duties and authority of vice president  in the state structure system of Republic Indonesia is not rigidly stated in the constitution, in spite of the previous amandment of the constitution. Therefore, the account of justify of vice president is not clear. Vice president is still regarded as the second person. Key words : Vice president